Measure of Zeta Potential of Titanium Pillared Clays - Zacur Vercellone, Sofia Susana (2015)
The change of the zeta potential, ζ, with the pH as well as the isoelectric point of a charged particle are electrokinetic properties that characterize it. The TiO2 pillared clays are very interesting materials because of their ability to adsorb polluting substances and their potential to be used as photocatalyst in their degradation. That is why the preparation and characterization of these materials are important to improve their use in environmental chemistry. The aim of this work was the comprehension of the electrokinetic behavior of TiO2 pillared clays by the determination of ζ and characterization of two TiO2 pillared clays and two TiO2pillared organoclays prepared using different acid of hydrolysis, as well as in the original clay. The pillared organoclays presenteda lower variation in the shape and the slope of the curves and in the IEP respect to that of the original clay. This behavioris due to the fact that the pillared organoclays has a lower content of pillars than that of the TiO2pillared clays, because the alkylamonium cation blocks part of the available exchanging sites for the anchored of the TiO2.xH2O species. When these materials are calcined the number of negative charged sites neutralized by TiO2will be minor than that observed for the pillared clays prepared in absence of surfactant. In consequence we can say that the preparation of TiO2 pillared clays using alkylammonium allows to obtain materials with a controlled superficial charge and porosity that can favor the access of polluting substances and their subsequent degradation in photatalytic treatments process.